COMPANY PERFORMANCE OF MICRO SMALL AND MEDIUM ENTERPRISES BY OPEN CHARTER DIRECT FLIGHT FROM CHINA TO MANADO (CASE STUDY: JENDELA INDONESIA SOUVENIR SHOP) - Mewengkang, Osfred Yuda; Saerang, David P.E.; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2019)
Abstract: China is a country with the largest population in the world and economic condition making China as an potential market share, especially in tourism sector. Currently tourism sector is being promoted by Manado’s Government to attract Chinese tourists to visit Manado by established open charter direct flight from China to Manado in 2016. This research aims to find out impacts of open charter direct flight from China to Manado on MSME company performance. The researcher used sales performance, number of consumers, employment, tourist spending, and product development as the indicator in this research. This study uses qualitative method with purposive sampling through in-depth interview. This research conduct interview with 7 MSME as the respondent. Finding shows that Chinese tourists in Manado give impacts to company performance of MSME in Manado, but not all MSME realized significant impact, it depends on the product or commodities. Impacts on company performance still not optimal yet realized by MSME in Manado. From the results, it is recommended for the Government, tourism actors, MSME in Manado and future research purpose. Keywords: company performance, msme, entrepreneurship, tourism, open charter direct flight, souvenir shop